Classical Swine Fever Virus Infection Induces Endoplasmic Reticulum Stress-Mediated Autophagy to Sustain Viral Replication in vivo and in vitro - Zhu, Erpeng; Chen, Wenxian; Qin, Yuwei; Ma, Shengming; Fan, Shuangqi; Wu, Keke; Li, Wenhui; Fan, Jindai; Yi, Lin; Ding, Hongxing; Chen, Jinding; Zhao, Mingqiu (Frontiers in Microbiology, 2019)
Endoplasmic reticulum (ER) stress-mediated autophagy plays significant roles in replication and pathogenesis of many animal viruses. However, the relationship between ER stress, autophagy and viral replication during in vivo and in vitro infection of classical swine fever virus (CSFV) remains unclear. In this study, we established a pig model for CSFV infection and found that viral loads of CSFV differed in ten kinds of infected organs, and that the degree of tissue lesions was to some extent positively correlated with CSFV replication in vivo. Next, we found that CSFV infection not only induced ER stress and subsequently activated three unfolded protein responses (UPR) pathways including protein kinase R-like ER kinase (PERK), inositol requiring enzyme 1 (IRE1) and activating transcription factor-6 (ATF-6) pathways, but also triggered complete autophagy in main immune organs and partial nonimmune organs exhibiting severer pathological injuries and higher viral loads. However, only the IRE1 pathway and no autophagy were activated in some other nonimmune organs with slighter pathologies and lower viral loads. These results indicate a potential link between CSFV-induced ER stress and autophagy, both of which are associated with the CSFV replication in vivo. We further performed in vitro experiments and found that CSFV infection activates the PERK and IRE1 pathways and autophagy in cultured porcine kidney cell lines (PK-15) and macrophage cell lines (3D4/2), and pharmacological regulation of ER stress remarkably changed autophagic activities induced by CSFV, suggesting that CSFV-induced autophagy can be mediated by ER stress possibly via the PERK and IRE1 pathway. Furthermore, treatment with ER stress regulators significantly altered copy numbers of NS5B genes, expression of Npro proteins and viral titers in CSFV-infected cells or in cells treated with autophagy regulators prior to CSFV infection, suggesting the requirement of ER stress-mediated autophagy for CSFV replication in vitro. Collectively, our data demonstrate that CSFV induces ER stress-mediated autophagy to sustain its replication in vivo and in vitro, which may be one of the potential strategies exploited by CSFV for immune evasion. This finding will provide new insights into mechanisms of replication and pathogenesis of CSFV, and development of new strategies for controlling CSF.